Q. 194.1( 7 Votes )

<span lang="EN-US

Answer :

Let


Substitute t=a-x


dt=-dx.


Also when x=0, t=a and when x=a, t=0.


Hence,



Replacing t with x, we get



=RHS


Hence, .


Let


Using , we get




Adding (1) and (2), we get



Let cos x = t


-sin x dx=dt.


When x=0, t=1 and


when x=π, t=-1







Hence,


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Evaluate:<span laMathematics - Board Papers

Evaluate:

Mathematics - Board Papers

Using integrationMathematics - Board Papers

Evaluate:<span laMathematics - Board Papers

Evaluate:<span laMathematics - Board Papers

Evaluate:<span laMathematics - Board Papers